How Do Addressees Exploit Conventionalizations? From a Negative Reference to an ad hoc Implicature - Kronmüller, Edmundo; Noveck, Ira (Frontiers in Psychology, 2019)
A negative reference such as “not the sculpture” (where the sculpture is a name the speaker had only just invented to describe an unconventional-looking object and where the negation is saying that she does not currently desire that object) seems like a perilous and linguistically-underdetermined way to point to another object, especially when there are three objects to choose from. To succeed as a reference, it obliges listeners to rely on contextual elements to determine which object the speaker has in mind. Prior work has shown that pragmatic inference-making plays a crucial role in such an interpretation process. When a negative reference leaves two candidate objects to choose from, listeners avoid an object that had been previously named, preferring instead an unconventional looking object that had remained unnamed (Kronmüller, Noveck, Rivera, Jaume & Barr, 2017). In the present study, we build over these findings by maintaining our focus on the two remaining objects (second and third) as we systematically vary two features. With respect to the second object – always unconventional – we vary whether or not it has been given a name. With respect to the third object -- which is never named – we vary whether it is unconventional- or conventional-looking (imagine an object that clearly resembles a bicycle). As revealed by selection patterns and eye-movements in a visual-world eye-tracking paradigm, we replicate our previous findings that show that participants choose randomly when both of the remaining objects are unconventional-looking and unnamed and that they opt reliably in favor of the most nondescript (the unnamed unconventional-looking) object when the second object is named. We show further that (unnamed) conventional-looking objects provide similar outcomes when juxtaposed with an unnamed unconventional object. Nevertheless, effects emerging from the conventional (unnamed) case are not as strong as those found with respect to those reported when an unconventional object is named. In describing participants’ choices in the non-random cases, we propose that addressees rely on the construction of an ad hoc implicature that takes into account which object can be eliminated from consideration, given that the speaker did not explicitly name it.